PENGARUH PENDEKATAN ACTIVE LEARNING TERHADAP PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DALAM MEMBENTUK KARAKTER ISLAMI SISWA SMPN 4 TANJUNGPINANG-KEPULAUAN RIAU - Wirdatul Aini (TANJAK, 2022)
Abstract The study is triggered by the current students’ condition in the Islamic religious education class, which are mostly lack of participation, lack of activeness, and lack of acting with good character. To cope with the problems, this study implemented Active learning in Islamic religious education as a way to shape students’ Islamic characters in SMP N 4 Tanjungpinang, Kepulauan Riau. The research method used is a quantitative method with the type of survey research. The results of calculations from questionnaire data or questionnaire distribution state that there is a positive and significant influence between the X variable "active learning approach" on Islamic religious education learning in shaping the Islamic character of students at SMP Negeri 4 Tanjung Pinang. This is in accordance with the results of the calculation of a simple linear regression test, namely equal to 61.0%, while the rest is influenced by other variables not examined in this study. This finding indicates that the initial hypothesis is accepted. Another finding from this research is that there are religious programs implemented by schools which are also a supporting factor in shaping the Islamic character of students